APLIKASI RESIN BENING UNTUK KREASI AKSESORIS DI GRIYA CRAFITA COMMUNITY PURWOKERTO - Ari Asnani; Hartiwi Diastuti; Puji Lestari (LP2M Universitas Hasanuddin, 2021)
Abstract. Ipteks based Community Service has been carried out through the technology transfer of clear resin for accessories creation. The activity partner was the members of Griya Crafita Community Purwokerto. The activity's objectives were knowledge transfer of resin application to produce various accessories; technology transfer of resin application to make brooches, key chains, pendants, and refrigerator magnets; and technology transfer for adding pigment dyes, natural fillers, and synthetic fillers. The methods applied were socialization of activities; knowledge transfer of resin chemistry, resin formulation, and handling of resins; first training, which consisted of resin application for making brooches, key chains, pendants, and refrigerator magnets; second Training, which included adding pigment dyes, natural fillers, and synthetic fillers; independent practices by GCC Purwokerto members; and evaluation of the activities. The main results of the implementation IPTEKS are the increasing partner knowledge of the application of resin as a raw material for a variety of accessories; and the production of resin-based accessories in the form of brooches, key chains, pendants, and fridge magnets. Abstrak. Pengabdian kepada masyarakat berbasis ipteks telah dilakukan melalui kegiatan transfer teknologi aplikasi resin untuk kreasi aksesoris. Sebagai mitra adalah Griya Crafita Community Purwokerto. Tujuan kegiatan adalah transfer pengetahuan aplikasi resin untuk produksi ragam aksesoris; transfer teknologi aplikasi resin untuk pembuatan bros, gantungan kunci, liontin, dan magnet kulkas; dan transfer teknologi penambahan bahan pewarna pigmen, bahan pengisi alami, dan bahan pengisi sintetis. Metode penerapan ipteks terdiri dari enam tahapan kegiatan, yaitu osialisasi kegiatan; transfer pengetahuan dasar kimia resin, formulasi resin, dan penanganan resin; pelatihan aplikasi resin untuk pembuatan bros, gantungan kunci, liontin, dan magnet kulkas; pelatihan aplikasi transfer teknologi penambahan bahan pewarna pigmen, bahan pengisi alami, dan bahan pengisi sintetis; praktek mandiri oleh anggota GCC Purwokerto; dan valuasi kegiatan. Hasil pelaksanaan pengabdiaan ini adalah peningkatan pengetahuan dan ketrampilan mitra terhadap aplikasi resin sebagai bahan baku beragam aksesoris; serta produk aksesoris berbasis resin berupa bros, gantungan kunci, liontin, dan magnet kulkas.